Stability Constants of Ternary Complexes of Cu(II) and Ni(II) With N-Substituted Anthranilic Acids with Some Amino Poly Carboxylic Acids - Krishna Rao, B.; Laxmi, K.; Sarala Devi, Ch. (Asian Journal of Chemistry, 2010)
Potentiometric titrations were carried out for the formation of binary and ternary complexes of the type MA, ML and MAL where M = Cu(II) and Ni(II), A = iminodiacetic acid (IMDA), hydroxyiminodiacetic acid (HIMDA) or nitrilotriacetic acid (NTA) and L = N-methyl anthranilic acid (N-Me.An.A.), N-butyl anthranilic acid (N-Bu.An.A.) or N-phenyl anthranilic acid (N-Ph.An.A.) at 303 K and 0.1 M ionic strength in 50 % (v/v) ethanol-water medium. The stabilities of the ternary metal complexes have been quantitatively compared with the stabilities of the corresponding binary metal complexes determined under identical experimental conditions and expressed in terms of Δ log K. The Δ log K values calculated for all the systems indicate the extent of stabilization and destabilization of ternary chelates compared to their binary chelates. The order of stability constants of ternary systems with respect to polyamino carboxylic acids is found to be IMDA > HIMDA > NTA. These were explained in the light of their basicities, charge neutralization and electrostatic interactions.